2010
DOI: 10.1007/s00442-010-1727-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific scaling of natural mortality in fish: the paradigmatic case of the European eel

Abstract: Identifying factors and processes influencing natural mortality is fundamental to the understanding of population dynamics. Metabolic theory of ecology and experimental studies at the cross-species level suggest the existence of general patterns linking natural mortality to body mass and temperature. However, there is scant evidence that similar relationships also hold at the intra-specific scale, possibly because of the relatively narrow range of sizes and temperatures experienced by most species and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 48 publications
4
70
0
3
Order By: Relevance
“…Metabolic theory of ecology has been proposed as a framework for evaluating local adaptation (Munch and Salinas 2009). However, limited information is available regarding intraspecific variation in mortality rates (Bevacqua et al 2011). We found a strong latitudinal gradient in common carp population characteristics including longevity and mortality rates that closely follow latitudinal variation in metabolic rates.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic theory of ecology has been proposed as a framework for evaluating local adaptation (Munch and Salinas 2009). However, limited information is available regarding intraspecific variation in mortality rates (Bevacqua et al 2011). We found a strong latitudinal gradient in common carp population characteristics including longevity and mortality rates that closely follow latitudinal variation in metabolic rates.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that it has dropped to a mere 1 % of its 1970 levels (Dekker 2003;Bevacqua et al 2011). Currently, the species is outside the limits of biological safety and, consequently, it has been placed on the Red List of endangered species in Europe (Belpaire et al 2009;Prigge et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the direct effect of the highest temperatures on eel growth in this system, the highest thermal environments might lead to negative side effects on eel growth from the related environmental variables. Bevacqua et al (2011) suggested the possibility that the natural mortality rates of eels increase with temperature. In addition to this, river flow in the Gironde system had a strong negative relationship with temperature in recent decades (r 2 = 0.37, p < 0.001; data provided by Centre Nucléaire de Production d'Électricité du Blayais).…”
Section: Discussionmentioning
confidence: 99%